2011
DOI: 10.1590/s0066-782x2011005000063
|View full text |Cite
|
Sign up to set email alerts
|

Alterações vasculares em ratos obesos por dieta rica em gordura: papel da Via L-arginina/NO Endotelial

Abstract: Background: Mechanisms underlying vascular abnormalities in obesity remain to be completely clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 33 publications
3
21
0
3
Order By: Relevance
“…So, augmented vasodilation in obese group could be attributed to an increase of NO release and this is in contrast with previous studies which have reported a decrease of endothelium-dependent relaxation to vasodilators in obesity 32-35. However an increase of eNOS activation 36 and improvement of endothelial-L-arginine/NO pathway have been previously described 16. These effects have been related with hyperinsulinemia and hyperleptinemia associated with obesity since both insulin and leptin increase endothelial NO production 16.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…So, augmented vasodilation in obese group could be attributed to an increase of NO release and this is in contrast with previous studies which have reported a decrease of endothelium-dependent relaxation to vasodilators in obesity 32-35. However an increase of eNOS activation 36 and improvement of endothelial-L-arginine/NO pathway have been previously described 16. These effects have been related with hyperinsulinemia and hyperleptinemia associated with obesity since both insulin and leptin increase endothelial NO production 16.…”
Section: Discussionmentioning
confidence: 73%
“…There are studies demonstrating an increase 15, no change 16 or a decrease in reactivity to agonist vasoconstrictors 17. Differences in pharmacological responses of blood vessels might be receptor-mediated or due to nonspecific responses of smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Porém, no presente estudo, todos os grupos iniciaram o protocolo de treinamento e suplementação proteica com valores próximos a 0,6 aumentando para 0,8. Para Angéloco et al 28 , o IMC pode estimar de forma confiável a gordura corporal em rato, sendo diretamente proporcional ao seu crescimento, já o índice de Lee é considerado menos sensível, pois animais com elevada quantidade de massa muscular podem apresentar elevado índice de Lee mesmo que a gordura corporal não seja excessiva [19][20][21] .…”
Section: Discussionunclassified
“…O índice de adiposidade (IA%) foi calculado através da relação entre a gordura corporal total e o peso corporal final multiplicado por 100 20 .…”
Section: Protocolo Experimentalunclassified
See 1 more Smart Citation